2014
DOI: 10.1002/2327-6924.12033
|View full text |Cite
|
Sign up to set email alerts
|

Basal-bolus insulin therapy and glycemic control in adult patients with type 2 diabetes mellitus: A review of the literature

Abstract: Purpose To present an integrative review related to basal‐bolus insulin therapy and glycemic control in adult patients with type 2 diabetes mellitus. Data sources A search of the Cochrane, Medline (first search and PubMed), and CINAHL electronic databases was conducted from 2004 through 2011 using the search terms “basal‐bolus insulin therapy, sliding scale insulin, glycemic control, and adult.” Conclusions Comparisons were made of glycemic control, safety, adverse events, body weight, and insulin dose showing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Present data on insulin use in LTC residents with type 2 diabetes is meager with great variation in treatment regimen indicating a need for data from new randomized, prospective trials. 7,10 Of 440 trials investigating treatments for type 2 diabetes, 65.7% excluded older adults, and only 1.4% were designed to study the elderly 28 ; the age exclusion appears higher than that reported for other age-related diseases, limiting the value of findings when treating older LTC diabetic residents with complex problems. 28 One survey of residents with type 2 diabetes in 13 nursing homes observed that SSI was used in 58% of these residents and that only 15% of the homes had treatment algorithms to manage diabetes mellitus.…”
Section: Studies On Ssi and B-bi Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Present data on insulin use in LTC residents with type 2 diabetes is meager with great variation in treatment regimen indicating a need for data from new randomized, prospective trials. 7,10 Of 440 trials investigating treatments for type 2 diabetes, 65.7% excluded older adults, and only 1.4% were designed to study the elderly 28 ; the age exclusion appears higher than that reported for other age-related diseases, limiting the value of findings when treating older LTC diabetic residents with complex problems. 28 One survey of residents with type 2 diabetes in 13 nursing homes observed that SSI was used in 58% of these residents and that only 15% of the homes had treatment algorithms to manage diabetes mellitus.…”
Section: Studies On Ssi and B-bi Therapiesmentioning
confidence: 99%
“…A recent review suggested that B-BI use in inpatient and outpatient settings is associated with decreased hospitalizations, decreased length of stay, lower health care costs, reduced hyper-and hypoglycemic episodes, and improved outcomes. 10 An earlier prospective, randomized trial in 130 hospitalized patients with type 2 diabetes, suggested that B-BI therapy achieves superior glucose control compared with SSI therapy. 11 The use of the basal insulin analog, glargine, as a component of B-BI therapy has been determined safe in clinical practice 12 in the young and old 13 ; the addition of insulin aspart (or other analogs) provides a bolus or prandial component to provide glucose control similar to human insulin.…”
mentioning
confidence: 99%
“…The complexity of a sliding scale insulin regimen could potentially lead to poor patient outcomes including increased readmissions, adverse drug events, and inappropriate glycemic control. 10 Currently, there are limited data available that examine the readmission outcomes of sliding scale insulin compared to basal-bolus insulin in this specific patient population. A prospective study did find that the use of sliding scale insulin in older patients was associated with an increased risk of hospitalization (odds ratio [OR]: 4.97).…”
Section: Introductionmentioning
confidence: 99%